CropSNPdb: a database of SNP array data for Brassica crops and hexaploid bread wheat. (28th January 2019) - Scheben, Armin; Verpaalen, Brent; Lawley, Cynthia T.; Chan, Chon‐Kit K.; Bayer, Philipp E.; Batley, Jacqueline; Edwards, David
Summary: Advances in sequencing technology have led to a rapid rise in the genomic data available for plants, driving new insights into the evolution, domestication and improvement of crops. Single nucleotide polymorphisms (SNPs) are a major component of crop genomic diversity, and are invaluable as genetic markers in research and breeding programs. High‐throughput SNP arrays, or 'SNP chips', can generate reproducible sets of informative SNP markers and have been broadly adopted. Although there are many public repositories for sequencing data, which are routinely uploaded, there are no formal repositories for crop SNP array data. To make SNP array data more easily accessible, we have developed CropSNPdb (http://snpdb.appliedbioinformatics.com.au ), a database for SNP array data produced by the Illumina Infinium™ hexaploid bread wheat ( Triticum aestivum ) 90K and Brassica 60K arrays. We currently host SNPs from datasets covering 526 Brassica lines and 309 bread wheat lines, and provide search, download and upload utilities for users. CropSNPdb provides a useful repository for these data, which can be applied for a range of genomics and molecular crop‐breeding activities. Significance statement: Genotyping arrays are important for generating genome‐wide markers to map traits and assess genetic diversity in crops. We describe CropSNPdb, a web‐based platform hosting wheat and Brassica genotype array data to accelerate breeding and gene discovery.